Represi dan Resistensi Negara dalam Novel Laut Bercerita Karya Leila S.Chudori - Tasha Maulina Ferizal; Nessa Riska Pangesti (Persona: Kajian Bahasa dan Sastra, 2024)
The purpose of this study is to provide a detailed explanation of: (1) the novel "Laut Bercerita" by Leila S. Chudori explores the presence of repressive state apparatus (RSA), (2) the novel "Laut Bercerita" by Leila S. Chudori explores the concept of the ideological state apparatus (ISA), (3) The novel "Laut Bercerita" by Leila S. Chudori explores forms of direct and indirect resistance. This research uses a qualitative approach and uses a descriptive method. The novel "Laut Bercerita" by Leila S. Chudori, the 52nd edition published by KPG (Gramedia Popular Library) is a source of data and an object of research. The data in this study are in the form of words, phrases, clauses, and sentences taken from the narrator's exposition and the dialogues of the characters in the novel Laut Bercerita by Leila S. Chudori. Based on the results of the study, the following were found. First, there is a form of repressive state apparatus (RSA) in the novel Laut Bercerita by Leila S. Chudori which includes: (1) persecution 11 data, (2) intimidation 14 data, (3) oppression 4 data. The two forms of ideological state apparatus (ISA) in the novel Laut Bercerita by Leila S. Chudori include: (1) family 10 data, (2) education 3 data. The third resistance in the novel Laut Bercerita by Leila S. Chudori (1) directly 3 data, (2) indirect 1 data.